DAMPAK PANDEMI COVID-19 TERHADAP PERUBAHAN SOSIAL PADA ANAK - Theguh Saumantri (Pusat Studi Gender dan Anak, 2022)
This study aims to outline the impact of the COVID-19 pandemic on social change in children. Children as social actors have changed from their routines during the covid-19 pandemic, such as: not being at school, learning remotely virtually, doing activities at home, not meeting physically with their friends, and getting used to maintaining their health following the covid-19 health protocol. Another situation faced by children is experiencing separation from parents or caregivers because parents are in isolation or die because they are positive for covid-19, and parents cannot return home due to social distancing policies. This research was qualitative through library research, which included field research with observations, documentation, and interviews. This study found that the situations and conditions that occurred during the covid-19 pandemic impacted the social realm of children's growth and development. These situations can positively and negatively impact child development and children's social welfare problems.